The Simulation of Car Impact at Different Speeds by Abaqus and ANSYS Software, Study the Results, and Development of an Appropriate Analytical Relationship - Seyyed Amirreza Abdollahi, Alireza Ghiasvand, Seyyed Amirmohammad Mousavi (Mathematical Statistician and Engineering Applications, 2023)
The aim of this paper is to simulate the impact (crash/collision) of a car at different speeds by Abaqus and ANSYS software, and the obtained results were analyzed to developan appropriate analytical relationship. To ensure the accuracy and reliability of the results ofthe present paper, 5 car models were analyzed in 5 modes. At the beginning, the geometric model includes the body and the chassis of a Camaro car was modeled by Abaqus software along with spring and damper constraints. The body and chassis were designed and assembled in SolidWorks software. After importing the model into the Abaqus software, some errors were encountered due to the use of the standard intermediary format, which was repaired and fixed for proper meshing. Finally, things like tension, deformation, energy, etc. were compared and an analytical relationship between energy and impact speed was developed for the car body by MATLAB software. In the second mode, a Peugeot 206 car was analyzed by ANSYS software. In this section, by using models designed for the Peugeot 206 car, converting the CAD models into importable models in ANSYSsoftware, and designing a solid (rigid) wall for impacting the car to it, the required models were analyzed. Also, in this mode, the things like reliability coefficient values based on Mohr-Coulomb theory, von Mises stress by the analyzed car, maximum equivalent stress, and plastic strain in the analyzed car were investigated. Then the relevant diagrams were analyzed. In the third mode, an Audi TT car was examined. Here, Inventor software was used to design the geometric model (unlike before). After modeling the designs in Inventor software, the model was analyzed with Abaqus software. In the fourth mode, a Sedan car was modeled as 3D in CATIA software and its impact to a solid wall was modeled in ANSYS software. In the fifth mode, a BMW 20 series car was tested, whose initial model including body and chassis were prepared in the generative shape design of CATIA. CATIA V5-6R2016 Associative Interface software was used to call the model in Abaqus software.